THE IMPACT OF BRAND EVALUATION, SATISFACTION, AND TRUST TO BRAND LOYALTY : A CASE STUDY OF THE INDONESIAN SMARTPHONE INDUSTRY - Wilson, Nicholas; Makmud, Stanley Tulus (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2018)
In this modern time , in electronic business especially in smartphone have an intense competition make any brand can’t avoid the competitors. The demand of the smartphone based on the company that create a product that have a benefit to the consumer. But in Indonesia things that make a product have a big interest because of trust and satisfaction that Indonesia’s people get. Although some of them never using it. But they get trust from people who have the smartphone. So brand evaluation from smartphone brands depends on consumer that use the product. In Indonesia things that make a product have a big interest because of trust and satisfaction that Indonesia’s people get. Although some of them never using it. In this research , the researcher use iphone 7 as an object in this study. Authors used a questionnaire method. This method had an advantage that a researcher can save time and money. The list of questions is arranged according to indicators from past research. Data that have been collected are analyzed using Partial Least Squares-Structural Equation Modelling (PLS-SEM) method with the help of SmartPLS 3.2.4 software. In this research respondent are Apple owner in Jakarta which is 257 respondents obtained using offline questionnaires. The result of this study indicates that there a direct relationship between brand evaluation, satisfaction and trust to brand loyalty. While brand relationships had no relationship to brand loyalty. Penelitian ini dilakukan untuk mengungkap dampak evaluasi merek, kepuasan, dan kepercayaan terhadap loyalitas merek di industri smartphone Indonesia. Penelitian ini menerapkan metode survei, di mana kuesioner digunakan sebagai instrumen untuk mengumpulkan semua data dari responden. Sebanyak 300 responden berpartisipasi dalam penelitian ini, di mana, setelah penilaian lebih lanjut, semua data dapat dianggap valid dan dapat diandalkan. Semua data yang telah dikumpulkan dan dinilai kemudian dianalisis menggunakan metode Partial Least Squares-Structural Equation Modeling (PLS- SEM), menggunakan perangkat lunak Smart PLS 3.2.7. Berdasarkan hasil analisis data, dapat disimpulkan bahwa evaluasi merek, kepuasan, evaluasi merek, dan kepercayaan memiliki dampak positif pada loyalitas merek.Kata kunci: evaluasi merek, kepuasan, kepercayaan, hubungan merek, loyalitas merek